Things That Make You Go Hmmm: Unmaking of the Racialized Self in a Graduate School Classroom - Birk, Manjeet (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Using critical race theory’s notion of counter storytelling I use three situations within my life as a racialized woman in the academy to exemplify the practices and symptoms of institutionalized intersectionality. Using my stories and the many useful critiques of intersectionality, I discuss how institutionalized intersectionality is failing marginalized women because institutions are co-opting “outsider” language and imposing it on bodies of their choosing.